Effects of confinement on the coupling between nitrogen and band states in InGaAs1-xNx/GaAs (x ≤ 0.025) structures: pressure and temperature studies - Choulis, Stelios A.; Weinstein, Bernard A.; Hosea, Thomas Jeff Cockburn (My University, 2001)
We report photo-modulated reflectance studies under applied pressure and variable temperature, and related calculations, that probe the influence of N-related resonant anti-bonding states on the electronic structure of dilute III–N–V quantum wells (QWs). Three InyGa1—yAs1—xNx/GaAs multiple QW samples with N contents of 0–2.5% are investigated up to 85 kbar at 300 K, and for 300–10 K at 1 atm. While the temperature dependence is only minimally affected by the N content, the pressure shifts of the intersubband transition energies depend significantly on the percentage of N. The linear pressure coefficients are much smaller than those of the InGaAs band gap. A ten-band k · p model is in broad accord with the observed pressure dependence; the predicted non-linear shift is somewhat larger than measured
Keywords: Pressure; Temperature; Nitrogen